Agricultural dust explosions in 2001 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were nine dust explosions reported in the U.S. in 2001 according to Robert W. Schoeff, Professor Emeritus, Kansas State University, and Mavis Rogers, FGIS-USDA. This compares to 8 in 2000 and a tenyear average of 11.9 explosions.
Keywords: Grain dust; Dust explosions